2018
DOI: 10.1002/ajp.22751
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of hair plucking in captive bonobos (Pan paniscus) in North American zoos

Abstract: When primates exhibit hair loss and are observed to engage in self or social hair plucking (a rapid jerking away of the hair shaft and follicle by the hand or mouth, often accompanied by inspection, and consumption) the altered appearance, and behavior patterns are thought to reflect individual physiological, and psychological well-being. Hair loss and hair plucking occur in many captive primate species, including all of the great apes. We present the first survey of this behavior among captive bonobos (N = 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Dell'Anna et al (2022) reported that individuals spending more time isolated from their group perform scratching behavior more frequently than the other members. Hair plucking in captive rhesus macaques may be correlated with rearing history and sex (Brand and Marchant (2018). Females engaged in more hair-plucking behavior than the males, and those wild-born macaques raised in the zoo engaged in more hair-plucking than captive-born primates.…”
Section: Discussionmentioning
confidence: 99%
“…Dell'Anna et al (2022) reported that individuals spending more time isolated from their group perform scratching behavior more frequently than the other members. Hair plucking in captive rhesus macaques may be correlated with rearing history and sex (Brand and Marchant (2018). Females engaged in more hair-plucking behavior than the males, and those wild-born macaques raised in the zoo engaged in more hair-plucking than captive-born primates.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows us to thoroughly consider the effect sizes of predictors in the models. (Brand & Marchant, 2018;Burnham & Anderson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows us to thoroughly consider the effect sizes of predictors in the models. (Brand & Marchant, 2018 ; Burnham & Anderson, 2002 ). All data analyses were performed using R version 4.2.3 (R Core Team, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are also species differences in the type of abnormal behavior that is most commonly expressed. Coprophagy was reported to be the most common behavior in chimpanzees ( Pan troglodytes ; Birkett & Newton‐Fisher, 2011; Jacobson et al, 2016; Nash et al, 1999), while regurgitation/reingestion was the most common in bonobos ( Pan paniscus ; Brand & Marchant, 2018). Further, motor stereotypies, such as pacing, were the most common in macaques, mangabeys, and prosimians (Bellanca & Crockett, 2002; Crast et al, 2014; C. K. Lutz, 2018; C. Lutz et al, 2003; Pomerantz et al, 2012; Tarou et al, 2005), but motor stereotypies and abnormal appetitive behavior were reported to occur at an equal level in baboons ( Papio hamadryas spp .…”
Section: Risk Factorsmentioning
confidence: 99%